Urban regeneration for sustainable communities: A case study - McDonald, Sally; Malys, Naglis; Malienė, Vida (Technological and Economic Development of Economy, 2009)
Over the past few decades, cities have been subjected to severe social and economic pressures, which have had a disproportionate impact on the urban environment. Consequently, this has increased the concentration of the most deprived households in the worst urban neighbourhoods. The UK Governments have attempted to tackle the physical, social and economic consequences of these changes through a variety of mechanisms and policy initiatives with varying degrees of success. The current objective can be interpreted as an attempt to implement regeneration projects or create sustainable communities/places through multi‐agency or partnership programmes. The nature and extent of urban problems are now very well documented; there has been a considerable learning process in the development of different urban regeneration programmes. Over the 20th and the beginning of 21st centuries, the nature of urban regeneration policy has changed direction several times and has applied different focuses. Today, a “sustainable community” is a key issue in an ambitious Government programme “umbrella”. As an objective of the present programme, the UK Government introduced the Sustainable Community Plan in 2003, describing a vision of how our communities are to be developed over next 20 years economically, socially and environmentally, while respecting the needs of future generations. The paper assesses how closely the Regeneration Programme is aligned to the Sustainable Communities Plan. The research within several surveys focuses on sustainable communities and urban regeneration, both have certain parallels and functional overlaps.Miestų atgaivinimas darnioms bendruomenėms kurti: atvejo tyrimasSantrauka. Šiuo metu siekiama įdiegti atgaivinimo projektus ir sukurti darniąsias bendruomenes pasitelkiant partnerystės programas. Darniosios bendruomenės kūrimas yra viena svarbiausių problemų, analizuojamų JK vyriausybės programoje. 2003 m. JK vyriausybes sukurtame darniųjų bendruomenių plane pateikiama vizija, kaip mūsų bendruomenės turetų vystytis ekonomiškai, socialiai ir aplinkos atžvilgiu per ateinančius 20 metu, atsižvelgiant į ateities kartų gerovę ir poreikius. Analizuojama, kaip glaustai miestų atgaivinimo programa yra suderinta su darniųjų bendruomenių kūrimo planu. Tyrimai, pagrįsti tiesioginėmis apklausomis, įvertina darniųjų bendruomenių ir miestų atgaivinimo pletrą bei sąsajas.Reikšminiai žodžiai: darnumas, bendruomenė, atgaivinimas, atvejo tyrimas, Castlefields, JK.First published online: 21 Oct 2010